ANALISIS KORELASI KEMUNCULANSPREAD F DANSINTILASI IONOSFER DI WILAYAH BARATINDONESIA MENGGUNAKAN DATAIONOSFER AGAM KOTOTABANGSUMATERA BARAT - Putri Andini; Usman Malik; Asnawi Husin (JOURNAL ONLINE OF PHYSICS, 2020)
This reseach has been done to know the correlation between spread F appearance and scintillation ionosphere on west region Indonesia. The method has been used is data interpretation using computational way, then all of data is processed using matlab software. The occurance of spread F was minimum in 2008 with it value respectively around 45%. In 2011 the spread F was beginning to increase with it value respectively around 70%. The occurance of ionospheric scintilation was minimum in 2010 with it value respectively around 13%. These occurances were due to a minimum phase of solar activity. In 2013 the scintilation was beginning to increase with it value respectively around 75% in which the occurance was selected for S4 ≥ 0,6. The correlation level between spread F and scintilation is medium, because the value of R aquals 0,4 this case is be affected by solar activity. The value of R is 0 (no correlation) at weak solar activity and 0,6 at high solar activity.